(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Wireless Sensor Networking is a network of wireless sensor nodes deployed in an area. Wireless Sensor Network (WSN) system is built on an IEEE 802.15.4 wireless mesh network. The wireless sensor network consists of the sensor nodes. A wireless sensor network (WSN) is a wireless network using sensors to cooperatively monitor physical or environmental conditions such as humidity, pressure, temperature, sound, vibration. The reduction of energy overhead is a major challenge in wireless sensor networks. The idea of development of wireless sensor networks was initially motivated by military applications. A WSN provides a reliable, low maintenance, low power method for making measurements in applications where cabled sensors are impractical or otherwise undesirable. Wireless Sensor Networks are used for monitoring and collecting information from an unattended environment and for reporting events to the user. The communication overhead in cluster based protocol is much less than the Broadcast based method (BBM) based protocol as the velocity of nodes increases. The energy loss can be minimizing by reducing the communication overhead but it may lead to information loss during the transient behavior of WSN. We present work; the comparative evaluation of communication overhead for the wireless sensor network based of on clustering technique is carried out. Simulation a result indicates that cluster based protocol has low communication overheads compared with the BBM based protocol when sink mobility is high. The communication overheads can be reduced by increasing update time.